Bone calcium turnover, formation, and resorption in bromocriptine- and prolactin-treated lactating rats - Sutada Lotinun (2018)
To evaluate the effect of endogenous prolactin (PRL) on bone metabolism, we studied bone calcium turnover by the45Ca kinetic method and bone formation and resorption by bone histomorphometry and biochemical markers in 13-wk-old lactating Wistar rats. For 1 wk, the animals received daily administration of 0.9% NaCl (control) intraperitoneally, 6 mg of bromocriptine/kg of body wt intraperitoneally, or 6 mg of bromocriptine/kg of body wt plus 2.5 mg of ovine PRL/kg of body wt subcutaneously. Bromocriptine, a dopaminergic inhibitor of endogenous PRL secretion, significantly decreased calcium ion deposit rate and calcium resorption rate in femur, tibia, vertebrae 5 and 6, and sternum by 20-42%. By contrast, calcium resorption rate of the vertebrae and the sternum of the PRL-treated group was higher than that of controls, whereas the tibia and sternum exhibited a greater net loss of calcium. The suppression of bone calcium turnover in the bromocriptine-treated group was further supported by a significant decrease in the urinary deoxypyridinoline, a biochemical index of bone resorption, and the histomorphometric data, which showed changes indicative of suppressed bone resorption and formation. The histomorphometric data from the PRL-treated group were not different from those of the control group with the exception of an increase in the longitudinal growth rate. The results suggested a role of endogenous PRL in the stimulation of bone turnover during lactation.